How do you use the Product Rule to find the derivative of #y = x(x^2 - 2)^(3/2)#?
1 Answer
Explanation:
Your function can be written as the product of two other functions
#y = underbrace(x)_(color(orange)(f(x))) * underbrace((x^2-2)^(3/2))_(color(red)(g(x)))#
which means that you can differentiate it by using the product rule
#color(blue)(d/dx(f(x)) = [d/dx(f(x))] * g(x) + f(x) * d/dx(g(x)))#
In your case, the derivative of
#d/dx(y) = [d/dx(x)] * (x^2 - 2)^(3/2) + x * d/dx(x^2-2)^(3/2)#
Now, to find
#d/dx(u^(3/2)) = d/(du)u^(3/2) * d/dx(u)#
#d/dx(u^(3/2)) = 3/2 * u^(1/2) * d/dx(x^2 - 2)#
#d/dx(x^2-2)^(3/2) = 3/color(red)(cancel(color(black)(2))) * (x^2 - 2)^(1/2) * color(red)(cancel(color(black)(2)))x#
Plug this back into your target derivative to get
#y^' = 1 * (x^2-2)^(3/2) + x * [3x * (x^2 -2 )^(1/2)]#
This is equivalent to
#y^' = (x^2 - 2)^(1/2) * ( x^2 -2 + 3x^2)#
#y^' = (x^2 -2 )^(1/2) * (4x^2 - 2)#
If you want, you can write this as
#y^' = color(green)(2 * (2x^2 - 1) * (x^2 -2 )^(1/2))#